Advancements and applications of COX inhibitors: A detailed bibliometric analysis of trending topics and emerging themes - Razan Naji, Zeinah Almulhim, Yassir A. Almofti, Maryam Mahmoud, Mahmoud kandeel (Journal of Applied Pharmaceutical Science, 2025)
Cyclooxygenase (COX) inhibitors are an important aspect of pain and inflammation therapy. This study provides a comprehensive bibliometric analysis of COX inhibitor research in order to identify key patterns, themes, emerging topics, authors, journals, and worldwide collaboration networks. The Scopus database was used to search for research on COX inhibitors from inception to 2024. The study themes, co-authorship networks, citation patterns, and publication growth were analyzed using R bibliometric tools such as Bibliometrix and VOSviewer. The findings show a 17.82% rate of international collaboration among the 3,400 publications examined, which came from 1,219 journals and were produced by 13,993 authors. The annual growth in research production was 4.15 percent. Celecoxib and molecular docking were frequently referenced, and the research was primarily concerned with inflammation, cancer prevention, and COX-2 inhibition. The evolution of trend topics can be summarized as follows: from early 2000s foundational pharmacological investigations to mid-2000s selective COX-2 inhibitors with reduced side effects. Computational techniques like molecular docking, 3D-QSAR, and statistical approaches have lately gained popularity for optimizing drug discovery. COX inhibitor research is expected to focus on using AI-driven drug discovery to develop more selective and less hazardous drugs.
Keywords: Cyclooxygenase inhibitors, COX-2, bibliometric analysis, nonsteroidal anti-inflammatory drugs, celecoxib